Whither India? 1919 and the Aftermath of the First World War. Issue 2 (May 2019) - Ghosh, Durba
Abstract : As diplomats across the world gathered in Paris in spring 1919 to discuss the peace process, observers asked "Whither India?" Critics wondered how the British government could enact emergency laws such as the Rowlatt Acts at the same time as it introduced the Government of India Act of 1919, which was intended to expand Indian involvement in governing the British dominions on the Indian subcontinent. Because Britain presented itself as a liberal form of empire on the international stage, its willingness to suspend rule of law over its subjects appeared contradictory. India's support of the Allied powers allowed Indian moderates to represent India in Paris; during the war, Indian subjects had contributed over one million soldiers and suffered influenza, plague, and famine. The possibility of a new relationship between those governing and those being governed led many Indians to demand an adherence to the rule of law, a guarantee of civil liberties, and the foundations of a government that was for and by the Indian people. In a time of revolution in Russia, and assassinations by anarchists in Italy and France, it seemed foolhardy to repress radicals by censoring the press, preventing the right of individuals to assemble, or detaining suspects before they had committed any crimes. Lala Lajpat Rai, an Indian political activist who had been part of the progressive wing of the Indian National Congress, wrote from the United States, "India is a part of the world and revolution is in the air all the world over. The effort to kill it by repression and suppression is futile, unwise, and stupid."